Mortality of hospitalized patients with COVID-19: Effects of treatment options (vitamin D, anticoagulation, isoprinosine, ivermectin) assessed by propensity score matching, retrospective analysis - Plasek, Jiri; Dodulik, Jozef; Gai, Petr; Hrstkova, Barbora; Skrha, Jan; Zlatohlavek, Lukas; Vlasakova, Renata; Danko, Peter; Ondracek, Petr; Cubova, Eva; Capek, Bronislav; Kollarova, Marie; et al. (Biomedical papers, 2024)
Introduction. SARS-CoV-2 respiratory infection is associated with significant morbidity and mortality, especially in hospitalized high-risk patients. We aimed to evaluate the effects of treatment options (vitamin D, anticoagulation, isoprinosine, ivermectin) on hospital mortality in non-vaccinated patients during the 2021 spring wave in the Czech Republic. Methods. Initially, 991 patients hospitalized in the period January 1, 2021, to March 31, 2021, with PCR-confirmed SARS-CoV-2 acute respiratory infection in two university and five rural hospitals were included in the study. After exclusion of patients with an unknown outcome, a total of 790 patients entered the final analysis. The effects of different treatments were assessed in this cohort by means of propensity score matching. Results. Of the 790 patients, 282 patients died in the hospital; 37.7% were male and 33.3% were female. Age, sex, state of the disease, pneumonia, therapy, and several comorbidities were matched to simulate a case-control study. For anticoagulation treatment, 233 cases (full-dose) vs. 233 controls (prophylactic dose) were matched. The difference in mortality was significant in 16 of the 50 runs. For the treatment with isoprinosine, ivermectin, and vitamin D, none of the 50 runs led to a significant difference in hospital mortality. Conclusion. Prophylactic-dose anticoagulation treatment in our study was found to be beneficial in comparison with the full dose. Supplementation with vitamin D did not show any meaningful benefit in terms of lowering the hospital mortality. Neither ivermectin nor, isoprinosine was found to significantly decrease hospital mortality.
Keywords: SARS-CoV-2; COVID-19; vitamin D3; ivermectin; Isoprinosine; mortality; anticoagulation; propensity score matching